Light-weight high-thermal-conductivity aluminum alloy material and preparation method and application thereof

By optimizing the content ratio of elements such as Zn, Mn, Ti, Ce in aluminum alloys, and adopting solid solution heat treatment and aging treatment processes, the shortcomings of automotive aluminum alloy materials in strength, high temperature resistance and thermal conductivity are solved, and efficient strengthening and performance improvement of the materials are achieved.

CN119640108AInactive Publication Date: 2025-03-18LUNTE ENVIRONMENTAL TECH WUXI CO LTD
View PDF 1 Cites 0 Cited by

Patent Information

Application Number
CN202411730415.4
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-11-29
Publication Date
2025-03-18
Estimated Expiration
Not applicable · inactive patent

AI Technical Summary

Technical Problem

The existing automotive aluminum alloy materials have shortcomings in strength, high temperature resistance and thermal conductivity, which affect the structural integrity and performance of the engine.

Method used

By optimizing the content ratio of elements such as Zn, Mn, Ti, Ce in aluminum alloys, and using solid solution heat treatment and aging treatment processes, a multiphase strengthening mechanism is formed to improve the tensile strength and thermal conductivity of the material.

Benefits of technology

It significantly improves the tensile strength, thermal conductivity and high temperature resistance of aluminum alloy materials, and meets the long-term reliability and safety needs of automotive engines in high temperature environments.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure BDA0005160133800000101
    Figure BDA0005160133800000101
Patent Text Reader

Abstract

The invention provides a light-weight high-thermal-conductivity aluminum alloy material and a preparation method and application thereof, and belongs to the technical field of aluminum alloys, and the aluminum alloy material comprises the following components in percentage by mass: 0.32 to 0.66 percent of Zn, 0.14 to 0.35 percent of Mn, 0.10 to 0.37 percent of Ti, 0.12 to 0.47 percent of Ce, 0.02 to 0.18 percent of Si, 0.23 to 0.48 percent of Mg, 0.21 to 0.34 percent of Sc, 0.12 to 0.16 percent of Cu, 0.06 to 0.09 percent of Er, 0.008 to 0.022 percent of La, 0.01 to 0.04 percent of B, 0.012 to 0.025 percent of Co, 0.01 to 0.09 percent of Au, 0.08 to 0.12 percent of Zr, less than or equal to 0.05 percent of single content of other impurity elements, and the balance of aluminum. The total content of other impurity elements is smaller than or equal to 0.15%. The aluminum alloy material is excellent in comprehensive performance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The present invention belongs to the technical field of aluminum alloys, and in particular relates to a lightweight and highly thermally conductive aluminum alloy material and a preparation method and application thereof. Background Art

[0002] Automobile lightweighting refers to reducing the overall weight of the car by optimizing the design and using lightweight materials to improve fuel economy, reduce emissions, and enhance performance and safety. Automobile lightweighting is an important means to improve fuel economy, reduce emissions and enhance performance. With the development of new materials and new technologies, automobile lightweighting will further promote the sustainable development of the automobile industry. Aluminum alloy is the most abundant green metal in the earth's crust. It is not only light and has high specific strength, but also easy to form and has great recycling value. Therefore, it is regarded as one of the ideal materials for automobile lightweighting.

[0003] Although automotive aluminum alloys have many advantages, such as lightweight and good corrosion resistance, they still face some technical problems in practical applications: 1. Strength. The strength of aluminum alloys is usually lower than that of traditional steel, which may affect the structural integrity and durability of the engine. 2. High temperature resistance. The engine operates at a high temperature. Aluminum alloys may soften or creep at high temperatures, affecting their long-term performance. 3. Thermal conductivity: The thermal conductivity of aluminum alloys is different from that of steel, which may cause thermal stress and deformation problems, especially in high temperature environments.

[0004] Chinese patent application No.: 201710128882.3 discloses an aluminum alloy sheet for lightweight vehicle body and its preparation method. The aluminum alloy sheet for lightweight vehicle body has high bake hardening performance and good forming performance. By rationally optimizing the content of each element in the alloy and the heat treatment process, the aluminum alloy sheet has good comprehensive performance. However, the thermal conductivity of the aluminum alloy sheet is not ideal and cannot meet the market demand.

[0005] Therefore, there is an urgent need for a lightweight and highly thermally conductive aluminum alloy material and a preparation method and application thereof. Summary of the invention

[0006] The purpose of the present invention is to provide a lightweight and highly thermally conductive aluminum alloy material and a preparation method and application thereof.

[0007] In order to achieve the above object, the present invention provides the following technical solutions:

[0008] A lightweight and highly thermally conductive aluminum alloy material comprises the following components in percentage by mass: Zn 0.32-0.66%, Mn 0.14-0.35%, Ti 0.10-0.37%, Ce 0.12-0.47%, Si 0.02-0.18%, Mg 0.23-0.48%, Sc 0.21-0.34%, Cu 0.12-0.16%, Er 0.06-0.09%, La 0.008-0.022%, B 0.01-0.04%, Co 0.012-0.025%, Au 0.01-0.09%, Zr 0.08-0.12%, the individual content of other impurity elements is ≤0.05%, the total content of other impurity elements is ≤0.15%, and the balance is aluminum.

[0009] Furthermore, the mass percentage ratio of Zn:Mn:Ti is (0.4-0.5):(0.15-0.25):(0.15-0.20).

[0010] The automobile engine is one of the important parts of the automobile, and the performance of the materials used in it is directly related to the driving performance and safety performance of the automobile. The automobile engine is subjected to high mechanical loads during operation, so aluminum alloy materials are required to better withstand these mechanical loads, prevent material fatigue and fracture, and ensure the long-term reliability and safety of the engine. In the system of the present invention, when the mass percentage ratio of Zn:Mn:Ti is (0.4-0.5):(0.15-0.25):(0.15-0.20), the tensile strength of the aluminum alloy can be improved. Zinc can dissolve into the aluminum alloy matrix to form a solid solution, increase the lattice distortion of the matrix, and thus improve the strength of the material. Manganese can promote grain refinement and improve the strength of the material. Titanium can form fine dispersed phases with aluminum. These dispersed phases can hinder the movement of dislocations and improve the strength of the material. The combined action of zinc, manganese and titanium can form a multiphase strengthening mechanism, including solid solution strengthening, precipitation strengthening and grain refinement. These mechanisms work together. Within this ratio range, the role of each element is best exerted, the microstructure and performance of the material reach the optimal state, and the tensile strength of the aluminum alloy can be significantly improved.

[0011] Further, the sum of the mass percentages of Mn and Ce is (1-1.5) times the mass percentage of Zn.

[0012] During the operation of the engine, the temperature in the combustion chamber can reach several thousand degrees Celsius, and the temperature of the piston, cylinder block, cylinder head and other components will also be very high. Aluminum alloy materials with high thermal conductivity can quickly transfer heat from high-temperature areas to the cooling system, keeping the engine components within a safe operating temperature range. This helps to prevent overheating and avoid material performance degradation and damage. When the sum of the mass percentages of Mn and Ce in the present invention is (1-1.5) times the mass percentage of Zn, the thermal conductivity of the aluminum alloy material is more excellent. Analysis shows that manganese and cerium can form stable precipitated phases, which can be evenly distributed in the matrix, reducing obstacles to heat flow. The appropriate addition of zinc (Zn) can further optimize the distribution and size of the precipitated phases, ensuring the smooth flow of the heat conduction path. At the same time, the appropriate addition of zinc can increase the scattering of free electrons and phonons in the matrix, but excessive zinc will lead to too many precipitated phases and grain boundaries, increase scattering, and reduce thermal conductivity. When the mass percentage of zinc is (1-1.5) times the sum of the mass percentages of manganese and cerium, the scattering of free electrons and phonons can be balanced and the thermal conductivity path can be optimized. At the same time, the yield strength of the aluminum alloy material is improved under this condition.

[0013] Further, the mass percentage of Zn is less than the sum of the mass percentages of Ti and Ce.

[0014] When the engine works at high temperature, the mechanical properties of the material will change, which may lead to structural failure. Through experiments, it is found that in the system of the present invention, when the mass percentage of Zn is less than the sum of the mass percentages of Ti and Ce, the tensile strength of the aluminum alloy material under heat-resistant conditions can be improved. The addition of titanium and cerium can improve the high-temperature stability of the aluminum alloy and reduce the softening and creep of the material at high temperatures. The appropriate addition of zinc can further optimize the high-temperature performance of the material and ensure good strength and toughness at high temperatures. When the mass percentage of zinc is less than the sum of the mass percentages of titanium and cerium, the tensile strength of the aluminum alloy material under heat-resistant conditions is significantly improved. This is because within this ratio range, the role of each element is best exerted, and the microstructure and performance of the material have reached the best state.

[0015] A second aspect of the present invention provides a method for preparing a lightweight and highly thermally conductive aluminum alloy material, comprising the following steps:

[0016] (1) Ingredients: weigh the raw materials according to mass percentage;

[0017] (2) Melting: Mixing the raw materials and then melting them to obtain a melt;

[0018] (3) Refining: adding a refining agent to the melt for refining, standing for 15-20 minutes after refining, skimming off the surface scum, and obtaining a refined melt;

[0019] (4) Casting: The refined melt is injected into a mold preheated to 220-250℃ for casting, and then the first solution heat treatment and the first aging treatment are carried out in sequence to obtain an aging casting. The aging casting is placed at 530-535℃ again for solution treatment for 1-2h; the temperature is raised to 540-545℃, solution treatment is carried out for 6-8h, and water cooling is carried out at a water cooling temperature of 60-80℃ and a water cooling time of 100-140s to obtain a water-quenched casting; the water-quenched casting is placed at -110--115℃ for deep cooling treatment for 1-2h; then, it is placed at 140-145℃ for aging treatment for 3-4h; it is placed at -110--115℃ again for deep cooling treatment for 1-2h; finally, it is placed at 140-150℃ for aging treatment for 8-10h, and air-cooled to room temperature at an air temperature of 10-30℃ to obtain a lightweight and highly thermally conductive aluminum alloy material.

[0020] Furthermore, in step (2), the smelting temperature is 745-750° C., and the smelting time is 1-2 h.

[0021] Furthermore, in step (3), the refining agent is hexachloroethane gas, and the refining temperature is 710-715°C.

[0022] Furthermore, the injection molding conditions in step (4) are: injection molding at 690-700° C. and a speed of 2.0-2.2 m / s.

[0023] Furthermore, the conditions of the first solution heat treatment in step (4) are as follows: the temperature of the first stage is 250-300°C, and the time is 3-4h; the temperature of the second stage is 420-450°C, and the time is 7-8h; the temperature of the third stage is 500-520°C, and the time is 5-6h;

[0024] Furthermore, the conditions of the first aging treatment in step (4) are as follows: the temperature of the first stage is 150-170°C and the time is 9-10h; the temperature of the second stage is 210-220°C and the time is 3-4h.

[0025] The present invention improves the elongation after fracture of the aluminum alloy material by performing solution heat treatment and aging treatment on the aluminum alloy, and also optimizes the thermal conductivity and thermal stability tensile strength performance of the aluminum alloy by solution heat treatment and aging treatment.

[0026] A third aspect of the present invention provides an application of a lightweight and highly thermally conductive aluminum alloy material in the preparation of an automobile engine.

[0027] Compared with the prior art, the advantages and beneficial effects of the present invention are:

[0028] 1. In the present invention, when the mass percentage ratio of Zn:Mn:Ti is (0.4-0.5):(0.15-0.25):(0.15-0.20), the tensile strength of the aluminum alloy can be improved.

[0029] 2. When the sum of the mass percentages of Mn and Ce in the present invention is (1-1.5) times the mass percentage of Zn, the thermal conductivity of the aluminum alloy material is more excellent.

[0030] 3. In the system of the present invention, when the mass percentage of Zn is less than the sum of the mass percentages of Ti and Ce, the tensile strength of the aluminum alloy material under heat-resistant conditions can be improved.

[0031] 4. The present invention improves the elongation at break of the aluminum alloy material by performing solution heat treatment and aging treatment on the aluminum alloy, and also optimizes the thermal conductivity and thermal stability tensile strength properties of the aluminum alloy by solution heat treatment and aging treatment. DETAILED DESCRIPTION

[0032] The technical solutions in the embodiments of the present invention are described clearly and completely below. Obviously, the described embodiments are only part of the embodiments of the present invention, not all of them. Based on the embodiments of the present invention, all other embodiments obtained by ordinary technicians in this field without creative work are within the scope of protection of the present invention.

[0033] Example 1

[0034] The present embodiment provides a lightweight and highly thermally conductive aluminum alloy material, comprising the following components in mass percentage: Zn 0.45%, Mn 0.20%, Ti 0.20%, Ce 0.29%, Si 0.09%, Mg 0.33%, Sc 0.28%, Cu 0.14%, Er 0.08%, La 0.015%, B 0.03%, Co 0.019%, Au 0.07%, Zr 0.09%, the individual content of other impurity elements is ≤ 0.05%, the total content of other impurity elements is ≤ 0.15%, and the balance is aluminum.

[0035] The method for preparing the above-mentioned lightweight and highly thermally conductive aluminum alloy material comprises the following steps:

[0036] (1) Ingredients: weigh the raw materials according to mass percentage;

[0037] (2) Melting: The raw materials are mixed and then melted at a temperature of 748° C. for 1.5 h to obtain a melt;

[0038] (3) Refining: adding a refining agent to the melt for refining, wherein the refining agent is hexachloroethane gas, the amount of which is 0.5% of the weight of the melt, the refining temperature is 712° C., the melt is allowed to stand for 20 minutes after refining, and the surface scum is skimmed off to obtain a refined melt;

[0039] (4) Casting: The refined melt is injected into a mold preheated to 230°C for casting. The injection conditions are: injection at 695°C at a speed of 2.1 m / s; then the first solution heat treatment and the first aging treatment are carried out in sequence to obtain an aged casting. The aged casting is placed at 532°C again for solution treatment for 1.5 h; the temperature is raised to 542°C, solution treatment is carried out for 7 h, and water cooling is carried out at a water cooling temperature of 70°C and a water cooling time of 120 s to obtain a water-quenched casting; the water-quenched casting is placed at -112°C for deep cooling for 1.4 h; then, it is placed at 142°C for aging treatment for 3.5 h; it is placed at -112°C again for deep cooling treatment for 1.5 h; finally, it is placed at 144°C for aging treatment for 9 h, and air-cooled to room temperature, with an air temperature of 20°C, to obtain a lightweight and highly thermally conductive aluminum alloy material.

[0040] The conditions of the first solution heat treatment are: the temperature of the first stage is 270℃, the time is 3.5h; the temperature of the second stage is 440℃, the time is 7.5h; the temperature of the third stage is 510℃, the time is 5.5h;

[0041] The conditions of the first aging treatment are as follows: the temperature of the first stage is 160°C and the time is 9.5 h; the temperature of the second stage is 215°C and the time is 3.5 h.

[0042] Example 2

[0043] The present embodiment provides a lightweight and highly thermally conductive aluminum alloy material, comprising the following components in mass percentage: Zn 0.46%, Mn 0.25%, Ti 0.20%, Ce 0.30%, Si 0.11%, Mg 0.25%, Sc 0.28%, Cu 0.16%, Er 0.06%, La 0.008%, B 0.04%, Co 0.025%, Au 0.01%, Zr 0.12%, the individual content of other impurity elements ≤ 0.05%, the total content of other impurity elements ≤ 0.15%, and the balance is aluminum.

[0044] The method for preparing the above-mentioned lightweight and highly thermally conductive aluminum alloy material comprises the following steps:

[0045] (1) Ingredients: weigh the raw materials according to mass percentage;

[0046] (2) Melting: The raw materials are mixed and then melted at a temperature of 745° C. for 2 h to obtain a melt;

[0047] (3) Refining: adding a refining agent to the melt for refining, wherein the refining agent is hexachloroethane gas, the amount of which is 0.5% of the weight of the melt, the refining temperature is 710° C., the melt is allowed to stand for 20 minutes after refining, and the surface scum is skimmed off to obtain a refined melt;

[0048] (4) Casting: The refined melt is injected into a mold preheated to 250°C for casting. The injection conditions are: injection at 690°C at a speed of 2.0 m / s; then the first solution heat treatment and the first aging treatment are carried out in sequence to obtain an aged casting. The aged casting is placed at 530°C again for solution treatment for 2 h; the temperature is raised to 540°C, solution treatment is carried out for 8 h, and water cooling is carried out at a water cooling temperature of 60°C and a water cooling time of 140 s to obtain a water-quenched casting; the water-quenched casting is placed at -110°C for deep cooling for 2 h; then, it is placed at 140°C for aging treatment for 4 h; it is placed at -110°C again for deep cooling treatment for 2 h; finally, it is placed at 140°C for aging treatment for 10 h, and air-cooled to room temperature, with an air temperature of 10°C, to obtain a lightweight and highly thermally conductive aluminum alloy material.

[0049] The conditions of the first solution heat treatment are: the temperature of the first stage is 300°C and the time is 3h; the temperature of the second stage is 450°C and the time is 7h; the temperature of the third stage is 500°C and the time is 6h;

[0050] The conditions of the first aging treatment are as follows: the temperature of the first stage is 150°C and the time is 10 h; the temperature of the second stage is 210°C and the time is 4 h.

[0051] Comparative Example 1

[0052] The difference between this comparative example and Example 1 is: a lightweight and highly thermally conductive aluminum alloy material, comprising the following components in mass percentage: Zn0.25%, Mn0.10%, Ti0.40%, Ce0.09%, Si0.19%, Mg0.53%, Sc0.18%, Cu0.24%, Er0.08%, La0.03%, B0.015%, Co0.019%, Au0.02%, Zr0.14%, the individual content of other impurity elements is ≤0.05%, the total content of other impurity elements is ≤0.15%, and the balance is aluminum.

[0053] Comparative Example 2

[0054] The difference between this comparative example and Example 1 is: a lightweight and highly thermally conductive aluminum alloy material, comprising the following components in mass percentage: Zn0.65%, Mn0.10%, Ti0.10%, Ce0.29%, Si0.09%, Mg0.33%, Sc0.28%, Cu0.14%, Er0.08%, La0.015%, B0.03%, Co0.019%, Au0.07%, Zr0.09%, the individual content of other impurity elements is ≤0.05%, the total content of other impurity elements is ≤0.15%, and the balance is aluminum.

[0055] Comparative Example 3

[0056] The difference between this comparative example and Example 1 is: a lightweight and highly thermally conductive aluminum alloy material, comprising the following components in mass percentage: Zn0.25%, Mn0.30%, Ti0.20%, Ce0.39%, Si0.09%, Mg0.33%, Sc0.28%, Cu0.14%, Er0.08%, La0.015%, B0.03%, Co0.019%, Au0.07%, Zr0.09%, the individual content of other impurity elements is ≤0.05%, the total content of other impurity elements is ≤0.15%, and the balance is aluminum.

[0057] Comparative Example 4

[0058] The difference between this comparative example and Example 1 is: a lightweight and highly thermally conductive aluminum alloy material, comprising the following components in mass percentage: Zn0.25%, Mn0.20%, Ti0.40%, Ce0.19%, Si0.09%, Mg0.33%, Sc0.28%, Cu0.14%, Er0.08%, La0.015%, B0.03%, Co0.019%, Au0.07%, Zr0.09%, the individual content of other impurity elements is ≤0.05%, the total content of other impurity elements is ≤0.15%, and the balance is aluminum.

[0059] Comparative Example 5

[0060] The difference between this comparative example and Example 1 is that the conditions of the first solution heat treatment are: the temperature of the first stage is 220°C and the time is 5h; the temperature of the second stage is 400°C and the time is 5h; the temperature of the third stage is 530°C and the time is 3h;

[0061] Comparative Example 6

[0062] The difference between this comparative example and Example 1 is that the conditions of the first aging treatment are: the temperature of the first stage is 130° C. and the time is 7 h; the temperature of the second stage is 240° C. and the time is 6 h.

[0063] Comparative Example 7

[0064] The difference between this comparative example and Example 1 is: a lightweight and highly thermally conductive aluminum alloy material, comprising the following components in mass percentage: Zn0.45%, Mn0.20%, Ti0.20%, Ce0.29%, Si0.09%, Mg0.33%, Sc0.28%, Cu0.14%, Er0.08%, La0.015%, B0.03%, Co0.019%, Au0.07%, Zr0.09%, the individual content of other impurity elements is ≤0.05%, the total content of other impurity elements is ≤0.15%, and the balance is aluminum.

[0065] The method for preparing the above-mentioned lightweight and highly thermally conductive aluminum alloy material comprises the following steps:

[0066] (1) Ingredients: weigh the raw materials according to mass percentage;

[0067] (2) Melting: The raw materials are mixed and then melted at a temperature of 748° C. for 1.5 h to obtain a melt;

[0068] (3) Refining: adding a refining agent to the melt for refining, wherein the refining agent is hexachloroethane gas, the amount of which is 0.5% of the weight of the melt, the refining temperature is 712° C., the melt is allowed to stand for 20 minutes after refining, and the surface scum is skimmed off to obtain a refined melt;

[0069] (4) Casting: The refined melt is injected into a mold preheated to 230°C for casting. The injection conditions are: 695°C and a speed of 2.1 m / s. Then, the first solution heat treatment and the first aging treatment are carried out in sequence, and the melt is air-cooled to room temperature (air temperature 20°C) to obtain a lightweight and highly thermally conductive aluminum alloy material.

[0070] The conditions of the first solution heat treatment are: the temperature of the first stage is 270℃, the time is 3.5h; the temperature of the second stage is 440℃, the time is 7.5h; the temperature of the third stage is 510℃, the time is 5.5h;

[0071] The conditions of the first aging treatment are as follows: the temperature of the first stage is 160°C and the time is 9.5 h; the temperature of the second stage is 215°C and the time is 3.5 h.

[0072] Performance Testing

[0073] The aluminum alloy materials prepared in Examples 1-2 and Comparative Examples 1-7 were subjected to performance tests.

[0074] 1. Mechanical properties test: Referring to GB / T228.1-2010, the room temperature mechanical properties are tested on an AG-X100kN electronic universal testing machine.

[0075] 2. Thermal stability test: The test method is carried out in accordance with GB / T228.1-2010. All aluminum alloys are tested with a 50mm gauge extensometer, a tensile speed of 5mm / min, a holding temperature of 150℃, and a holding time of 100 hours to determine the tensile strength after heat treatment.

[0076] 3. Thermal conductivity: measured in accordance with GB / T30598-2014.

[0077] Table 1 Performance test results

[0078]

[0079] It can be seen from the above performance test results that the aluminum alloy materials of Examples 1-2 have excellent mechanical properties, high thermal conductivity, and good temperature resistance, especially the comprehensive performance of Example 1 is the most outstanding, which is mainly due to the synergistic effect of the component ratio and the preparation process.

[0080] However, the comparative examples are obviously inferior to the embodiments in the corresponding performance tests because they do not adopt the necessary technical solutions. In comparative example 1, the component ratio is changed, and it can be seen that the comprehensive effect of the aluminum alloy material decreases. In comparative example 2, the mass percentage of Zn, Mn, and Ti is changed, and it can be found that the tensile strength of the aluminum alloy decreases. In comparative example 3, the mass percentage of Mn, Ce, and Zn is changed, and it can be found that the thermal conductivity of the aluminum alloy material decreases. In comparative example 4, the mass percentage of Zn, Ti, and Ce is changed, and it can be found that the tensile strength of the aluminum alloy material under heat-resistant conditions decreases. The conditions of the first solution heat treatment of comparative example 5 and the first aging treatment of comparative example 6 are changed. In comparative example 7, only the first solution heat treatment and the first aging treatment are performed, and no subsequent treatment is performed. It can be found that the elongation after fracture of the aluminum alloy material decreases, and the thermal conductivity and thermal stability tensile strength performance also decrease. The above experimental results further prove the importance of the technical solution defined in the present invention for its technical effect.

[0081] The above is a preferred embodiment of the present invention. It should be pointed out that for ordinary technicians in this technical field, several improvements and modifications can be made without departing from the principles of the present invention. These improvements and modifications should also be regarded as the scope of protection of the present invention.

Claims

1. A lightweight and highly thermally conductive aluminum alloy material, characterized in that: The invention comprises the following components in mass percentage: Zn 0.32-0.66%, Mn 0.14-0.35%, Ti 0.10-0.37%, Ce 0.12-0.47%, Si 0.02-0.18%, Mg 0.23-0.48%, Sc 0.21-0.34%, Cu 0.12-0.16%, Er 0.06-0.09%, La 0.008-0.022%, B 0.01-0.04%, Co 0.012-0.025%, Au 0.01-0.09%, Zr 0.08-0.12%, the individual content of other impurity elements is ≤0.05%, the total content of other impurity elements is ≤0.15%, and the balance is aluminum.

2. The lightweight and highly thermally conductive aluminum alloy material according to claim 1, characterized in that: The mass percentage ratio of Zn:Mn:Ti is (0.4-0.5):(0.15-0.25):(0.15-0.20).

3. The lightweight and highly thermally conductive aluminum alloy material according to claim 2, characterized in that: The sum of the mass percentages of Mn and Ce is (1-1.5) times the mass percentage of Zn.

4. The lightweight and highly thermally conductive aluminum alloy material according to claim 3, characterized in that: The mass percentage of Zn is less than the sum of the mass percentages of Ti and Ce.

5. A method for preparing the lightweight and highly thermally conductive aluminum alloy material according to any one of claims 1 to 4, characterized in that: The following steps are involved: (1) Ingredients: weigh the raw materials according to mass percentage; (2) Melting: Mixing the raw materials and then melting them to obtain a melt; (3) Refining: adding a refining agent to the melt for refining, standing for 15-20 minutes after refining, skimming off the surface scum, and obtaining a refined melt; (4) Casting: The refined melt is injected into a mold preheated to 220-250°C for casting, and then the first solution heat treatment and the first aging treatment are carried out in sequence to obtain an aged casting. The aged casting is placed at 530-535°C again for solution treatment for 1-2 hours; the temperature is raised to 540-545°C, solution treatment is carried out for 6-8 hours, and water cooling is carried out at a water cooling temperature of 60-80°C and a water cooling time of 100-140s to obtain a water-quenched casting; the water-quenched casting is placed at -110--115°C for deep cooling for 1-2 hours; then, it is placed at 140-145°C for aging treatment for 3-4 hours; it is placed at -110--115°C again for deep cooling treatment for 1-2 hours; finally, it is placed at 140-150°C for aging treatment for 8-10 hours, and air-cooled to room temperature, with an air temperature of 10-30°C, to obtain a lightweight and highly thermally conductive aluminum alloy material.

6. The method for preparing a lightweight and highly thermally conductive aluminum alloy material according to claim 5, characterized in that: In the step (2), the smelting temperature is 745-750° C. and the smelting time is 1-2 h.

7. The method for preparing a lightweight and highly thermally conductive aluminum alloy material according to claim 5, characterized in that: The injection molding conditions in step (4) are: injection molding at 690-700° C. and a speed of 2.0-2.2 m / s.

8. The method for preparing a lightweight and highly thermally conductive aluminum alloy material according to claim 5, characterized in that: The conditions of the first solution heat treatment in step (4) are as follows: the temperature of the first stage is 250-300°C and the time is 3-4h; the temperature of the second stage is 420-450°C and the time is 7-8h; the temperature of the third stage is 500-520°C and the time is 5-6h.

9. The method for preparing a lightweight and highly thermally conductive aluminum alloy material according to claim 5, characterized in that: The conditions of the first aging treatment in step (4) are as follows: the temperature of the first stage is 150-170° C. and the time is 9-10 h; the temperature of the second stage is 210-220° C. and the time is 3-4 h.

10. Use of the lightweight and highly thermally conductive aluminum alloy material according to any one of claims 1 to 4 in the preparation of automobile engines.

Citation Information

Patent Citations

  • Aluminum alloy panel for automobile body lightweight and preparing method of aluminum alloy panel

    CN106917016A